In memoriam. Per Corrado Ferri (1940-2024) (Materiali di Estetica. Terza serie, 2024)
Gabriele Scaramuzza reflects on the philosophical and intellectual legacy of Corrado Ferri, highlighting their rich dialogues on historical, musical, and existential themes. The article, written in memoriam following Ferri’s death in 2024, intertwines personal anecdotes with scholarly dialogue, illustrating Ferri’s dynamic personality and diverse interests. This tribute emphasizes Ferri’s approach to life and learning, characterized by his curiosity and critical engagement with diverse cultural and philosophical issues. Scaramuzza portrays Ferri as a thinker who seamlessly integrated personal experiences into his scholarly pursuits, making significant contributions to philosophical discourse and mentoring.
Keywords: intellectual legacy; philosophy; Corrado Ferri